Interculturality and virtual education in a primary level educational institution in the district of Ayacucho, 2021 - Rojas Porras, Nolberto Claudio (2023)
Objective. Analyze interculturality in virtual education in a public educational center in the city of Ayacucho. Methods.The methodology used was classroom observation and semi-structured interviews with teachers, students and parents. The information obtained was subjected to a process of data reduction and analysis. Results. The main results indicate the limitations in the access and use of information and communication technologies by the teacher and students, as well as the adaptation of the content of the classes to the local reality by the teacher. Conclusions. These conditions have resulted in a greater "rapprochement" of the students with the people of their environment and the culture of their origin, which, instead of contributing to cultural dialogue and intercultural education, has rather fostered endoculturation.